DECISION SUPPORT SYSTEM FOR TOKO ANDA SUPPLIER SELECTION WITH THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Ricki Ardiansyah; Maha Rani; Revi Gusriva; Elmi Rahmawati (Kresnamedia Publisher, 2022)
Choosing a supplier or supplier is an important factor for running a business because suppliers can affect the availability of goods, quality, and profits from the business. However, the selection of suppliers is a complicated problem in business because of the many alternatives and criteria that are the determining factors in supplier selection and the difficulty of choosing the right supplier with objective criteria in a short time. To assist in the selection of suppliers in Toko Anda, an SPK is built that can help provide the best supplier recommendations from several alternatives based on the selection criteria provided by the shop owner so that the selection of suppliers in Toko Anda can be done quickly using the system and produces an objective supplier choice. In carrying out the decision-making process in this SPK, the method that will be used is SAW. In the calculation process, the SAW method performs a weighted summation of the alternatives against all the criteria that are the reference in determining suppliers. The criteria that determine this decision support system are quality, price, completeness, packaging, warranty, delivery time, service. based on the calculation process using the saw method, the supplier ranking results from several existing alternatives are obtained. The supplier ranking results from this decision support system can be used by Toko Anda owner as a reference in determining the supplier. From the results of the calculation process with SAW, the ranking of Supplier F with the highest value is 22, then Supplier E and Supplier B with a value of 21.4, then Supplier D with a value of 21, then Supplier A with a value of 20.6 and finally Supplier C with a value of 20.4. From this research on making SPK, the SAW method can provide a ranking of suppliers in Toko Anda with an objective and short time.